Stigma, coping strategies, and their impact on treatment and health outcomes among young men living with HIV in Vietnam: A qualitative study. - Nhu Kieu Tran; Bach Ngoc Vu; Jordan Susa; Mary DeSilva (Public Library of Science (PLoS), 2022)
Background Stigma affects persons living with HIV in myriad ways, including mental health, adherence to antiretroviral therapy, and retention in care, and may manifest at inter- and intra-personal levels. Youth are particularly vulnerable; those in vulnerable groups may experience multiple stigmas. In Vietnam, new HIV infections are rising among men in young age groups. To better understand the facets of stigma experienced by young men living with HIV in Vietnam, we conducted a qualitative study with youth and clinicians. Methods We conducted in-depth interviews with ten youth and two clinicians in Hanoi, querying experiences of inter- and intra-personal stigma, coping strategies, and disclosure. As a framework for further research, we developed a conceptual model based on our findings and the published evidence base which portrays interactions among HIV-related stigma, coping strategies, and ART adherence, care engagement, and health outcomes. Results Common themes that emerged from interviews with youth included extensive internalized/self-stigma and perceived stigma, yet limited experienced interpersonal stigma due to non-disclosure and avoidant coping strategies. Within different types of relationships or contexts, youth used different strategies. Non-disclosure with family, friends, and workplaces/school, and avoidance of romantic relationships and health care were common. Mental health and social support appeared to be mediating factors between coping strategies and health outcomes. Conclusions Validation of this model of mechanisms of the impact of stigma for youth will require further research with larger samples. In the meantime, public campaigns to increase public awareness related to HIV should be implemented in Vietnam. Critical support for youth and their mental health should involve approaches tailored to the individual, taking into account context and personal capacity, including adequate time to prepare psychologically for disclosure. Some strategies for safe and effective disclosure are suggested.